Evaluation of Different Sweetener on the Production of Kamias Prunes - Usita, Normalina (Studies in Technology and Education, 2026)
The study focused on the development and evaluation of different sweetener on the production of kamias prunes using white sugar, washed sugar, brown sugar, and molasses, to determine their effects on the product characteristics in terms of taste, texture, aroma, and appearance. The research employed experimental design wherein kamias fruits were processed into prunes using the four different sweetener treatments under the same preparation and processing production. Descriptive evaluation was conducted to assess variations in sensory and physical attributes across treatments. Results revealed that the type of sweetener significantly influenced the characteristics of kamias prunes. The findings indicate that each sweetener contributes distinct sensory qualities, confirming its role in product development. It is concluded that sweetener selection is a critical factor in determining the quality of kamias prunes, and it is recommended that further studies be conducted to optimize formulations for possible commercialization.